Analisis Rasio Keuangan Sebagai Alat Penilaian Untuk Mengukur Kinerja Keuangan Pada Pt. Nyata Grafika Media Surakarta Periode 2012-2014 - Niyanti, Maya Andi, Dra. Chuzaimah,M.M (2016)
The problem in this study is whether the financial performance of PT. Graphic Media has been real good Surakarta quite efficient when seen from analysis of liquidity, activity and profitability. The data used in This research is secondary data from PT. Real Graphic Media Surakarta. Sources of data in the form of financial statements. Real Graphic Media Surakarta years 2012-2014. Analysis of the ratio used is the ratio of liquidity, activity ratios and profitability ratios. Based on the research note that of the liquidity ratio analysis current ratio obtained calculation results are in the three years 2012-2014 the level of assessment is less good because it is less than 100%, the quick ratio in 2012-2014 all three are at the level of assessment is less well too. From the analysis it can be concluded that signifies the company's condition is unstable or tends to be low. Judging from the analysis of the results obtained activity ratio level accounts receivable turnover in 2012-2014 is located on the third level ratings less efficient. The average rate of aging years 2012-2014 is all three are at the level of assessment is not efficient because more than one week, indicates the company's condition is not good. Judging from the analysis profitability ratios profit margin calculation results obtained in 2012-2014 is located on the third level of efficiency. While ROA year 2012-2014 all three are at a level that is less than good. concluded that profitability ratios show that the ability to generate profits net of sales less well. This means that the company has the level of financial performance is not good, so the company still needs to to improve the performance of the company.